Petrogenesis and Experimental Petrology of Granitic Rocks - Johannes, Wilhelm; Holtz, Francois (Minerals, Rocks and Mountains, 1996)
This book deals with the petrogenesis of granitic rocks. It gives a summary and interpretation of experimental results obtained in synthetic and natural rock systems. The significance of water for the formation, intrusion and crystallization of granitic magmas forms an important part of the book. Emphasizing experimental aspects, the reader is provided with a thorough understanding of the evolution of granites, which is the most important type of rock of the continental crust.